(untitled) (Research, Society and Development, 2020)
The aim of the study was to compare performance indicators and the profile of mood states in young male beach volleyball athletes. The sample consisted of 50 athletes, with ages between from 15 to 17 years, who participated at the Youth School Games (JEJ). We filmed 16 games during the qualifying phase of JEJ, which we grouped into winners and losers. Higher scores with significant difference (p <0.01) were verified in all coefficients (serve, reception, setter, attack, block and dig) for the teams of the winning games. For mood states, significant differences were also found in total mood disturbance and fatigue with smaller values for the winning teams. We concluded all the skills of beach volleyball were important performance indicators of young male athletes of the sport. Thus, there was no discrepancy in any specific basis, but the balance of better performance pointed out the difference between the winning and losing teams in the first games of the tournament. In addition, it was noticed that mood states that impair performance were observed at lower levels in the winning teams.